Features of the Accused Defence in the First-Instance Court - Kolomoitsev, Mykola (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2024)
To ensure effective defense and uphold constitutional principles within criminal proceedings, this article examines specific features defense practice by counsel in first-instance proceedings. It emphasizes that counsel’s involvement in first-instance court, particularly during preparatory hearings and trial, is crucial to ensuring fair administration of justice. This article establishes that, during preparatory proceedings, counsel’s role focuses on formulating legal strategy, reviewing and verifying procedural documents, and ensuring defendant’s presence at trial. At trial, counsel plays pivotal role in examination of witnesses, protecting defendant’s interests, and ensuring comprehensive examination case circumstances. This article underscores that proper organization counsel’s participation at both stages significantly contributes to achieving objectives criminal proceedings—establishing truth and rendering lawful judgment
Keywords: Criminal proceedings, pre-trial investigation, defense, defense party, accused, court, representation